DEVELOPMENT OF HUMAN DIGESTIVE SYSTEM MODULE BY USING GUIDED DISCOVERY LEARNING FOR GRADE VIII SMP/MTs STUDENTS - Putri Adila Sari; Lufri Lufri (Universe, 2021)
Improving the quality of education aims develop the potential of students who can be done through the learning process. Learning aimed at students can study independently, actively, and creatively according to the demands of the 2013 curriculum. Learning process is not separated from the teaching materials used. So it is necessary to teach a module that can guide learners in the learning activities. This research is a development research by using a PLomp model with three stages: preliminary investigation, prototype development stage, and assessment stage. The object of research is guided Discovery learning module on human digestive system material for students of class VIII. The research subject is a student of class VIII SMPN 26 Padang. Module validated by 3 lecturers majoring in IPA FMIPA UNP. The result of the evaluation itself was obtained that the module is developed according to the assessed aspect. The results of the validity test are obtained the average validity value of the content feasibility aspect, the linguistic, the presentation and the graphing with an average value of 87.5% with valid criteria. It is thus concluded that the learning modules of human digestive systems with guided discovery learning are developed to have a valid Krieria.